External public debt of CARICOM member states 1990-2000 (CARICOM Secretariat GeorgetownGY, 2002)
Provides data on external public debt at both the regional level and details at the level of Member States. Presents data highlights on the overall debt situation of CARICOM excluding Barbados and Suriname, as well as for Member States.
Keywords: EXTERNAL DEBT